A precision time of flight readout system for the TORCH prototype detector. (1st May 2022) - Gao, R.; Bhasin, S.; Blake, T.; Brook, N.; Cicala, F.; Conneely, T.; Cussans, D.; Forty, R.; Frei, C.; Gabriel, E.; Gershon, T.; Gys, T.; et al.
Abstract: The TORCH detector provides low-momentum particle identification, combining Time of Flight (TOF) and Cherenkov techniques to achieve charged particle pi/K/p separation between 2–20 GeV/c over a flight distance of 10 m. The measurement requires a timing resolution of 70 ps for single Cherenkov photons. For precision photon detection, customised Micro-Channel Plate Photomultiplier Tubes (MCP-PMTs) with high precision TOF measurement electronics have been developed. The electronics measures time-over-threshold from the MCP-PMT and features a 10-Gigabit Ethernet readout. This paper reports the design and performance of a 5120-channel system which currently instruments a pair of MCP-PMTs, but has the capacity to read out ten customised MCP-PMT devices in the future.